Heinrich Zimmer : Coming into His Own - Case, Margaret H. (Book collections on Project MUSE., 2014)
Heinrich Zimmer (1890-1943) is best known in the English-speaking world for the four posthumous books edited by Joseph Campbell and published in the Bollingen Series: Myths and Symbols in Indian Art and Civilization, Philosophies of India, The Art of Indian Asia, and The King and the Corpse. These works have inspired several generations of students of Indian religion and culture. All the papers in this volume testify to Zimmer's originality and to his rightful place in that small group of great scholars who were part of the first generation to confront the end of Europea.